Polychlorinated biphenyls and arsenic in hepatocarcinogenesis - Painter, Jon Todd, author; Benjamin, Stephen A., advisor; Andersen, Melvin E., committee member; Gardner, Hank, committee member; Hanneman, William H., committee member (Colorado State University. Libraries, 2005)
Polyhalogenated aromatic hydrocarbons such as polychlorinated biphenyls (PCBs) and dioxins are worldwide environmental pollutants and potential human carcinogens. These chemicals may be found together and with other chemicals such as arsenic (As), a known human carcinogen, in hazardous waste sites. The carcinogenic mechanisms of these substances remain unclear and there have been few studies examining such mixtures. The aim of our studies was to examine these compounds as individual chemicals and in mixtures, in order to better understand their roles in carcinogenesis. We measured the activity of cytochrome P-450 1A1 (CYP1A1), a metabolizing enzyme induced in the liver after exposure to TCDD (2,3,7,8-tetrachlorodibenzo-p-dioxin), PeCDF (2,3,4,7,8-pentachlorodibenzofuran), the coplanar PCB 126 (3,3',4,4',5-pentachlorobiphenyl) and the noncoplanar PCB 153 (2,2',4,4',5,5'-hexachlorobiphenyl), as individual chemicals and in mixtures. We found supporting evidence for the additive toxic equivalency factor (TEF) approach to risk assessment for dioxin-like, aryl hydrocarbon receptor (AhR)-binding chemicals but found a greater-than-additive increase in CYP1A1 activity in mixtures of the AhR-binding PCB 126 and the non-binding PCB 153. We found evidence that increases in 4-hydroxy estrogen catechol metabolites induced by the dioxin-like chemicals may help explain the higher sensitivity of female rats to hepatocellular neoplasia. The second study explored the interactions between PCB 126 and As in hepatocarcinogenesis using a 24-week initiation-promotion-progression model in the rat. We evaluated promotion of preneoplastic foci using the marker glutathione-S-transferase placental form (GST-P) and progression using the markers transforming growth factor-alpha (TGFα) and transforming growth factor-beta receptor II (TGFβIIr). Exposure to PCB 126 resulted in increased relative area and number of GST-P+ and TGFα+ foci. Arsenic as a single agent had no significant effect on foci size or number compared to controls. Arsenic combined with PCB 126 resulted in decreased relative area of GST-P+ and TGFα+ hepatic foci compared with PCB 126 alone. This effect was more prominent earlier in the study at 16 weeks than later at 24 weeks, suggesting a time-dependent effect of arsenic as an anti-promoting and/or progressing agent. A subset of large preneoplastic foci was GST-P+, TGFα+, and TGFβII-r negative, suggesting the altered hepatocytes in these foci possess a more advanced phenotype.
Keywords: pathology; toxicology